Vihara Avalokitesvara Serang: Arsitektur dan Peranannya dalam Relasi Buddhis-Tionghoa dengan Muslim di Banten - Nurman Kholis (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2016)
The Vihara Avalokitesvara (a Buddhist place of worship) is located in Pama¬rican, Customs, Serang. This vihara is the oldest vihara in Banten and was built in the 16th century. Nuances of Chinese and Buddhist architecture may be seen in the dragon decoration among other things and in the menyeruapi burning paper of the pagoda and in the painting and sculpture of Kwan lm Pouw Sat, and the sculpture of Wie Tho Pou Sat. There is a large statue of the Buddha and a picture of the lotus flower. And yet there are Islamic nuances also. There is a relief depicting the wedding of Princess Ong Tin with Syarif Hidayatullah. This vihara is visited by many Muslims as well as by Buddhists. Keywords: Vihara, Buddha, Chinese, Islam, Banten Vihara Avalokitesvara berlokasi di Pamarican, Pabean, Serang. Vihara ini merupakan vihara yang tertua di Banten dan diperkirakan dibangun sekitar abad ke-16. Untuk mengungkapkan unsur-unsur etnis dan agama pada arsitektur vihara ini dianalisis secara semiotik. Berdasarkan analisis ini maka diketahui unsur-unsur bernuansa Tionghoa yaitu antara lain hiasan naga, tempat pembakaran kertas yang menyeruapi pagoda, lukisan dan patung Dewi Kwan Im, patung Kwan lm Pouw Sat, dan patung Wie Tho Pou Sat. Adapun unsur-unsur agama Buddha dalam vihara ini antara lain patung besar Buddha Gautama dan gambar bunga teratai. Selain itu juga terdapat unsur bernuansa Islam yaitu pada relief yang menggam¬barkan pernikahan Putri Ong Tin dengan Syarif Hidayatullah. Karena itu, vihara ini juga dikunjungi oleh banyak umat Islam. Kata Kunci: vihara, Buddha, Tionghoa, Islam, Banten